Studi kasus : Feline Panleukopenia Virus pada Kucing Abel - Albab, Ulul; Febrianth, Alvin; Hermawan, Intan Permatasari; Kurnianto, Ady (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2022)
A domestic cat with short hair, approximately three months old, was brought to the Tabby Pet Care clinic with complaints that the cat's owner had vomiting and diarrhea. The results of clinical examination showed a state of dehydration and swollen popliteal. Supportive examinations include hematological examinations and rapid test kits. Hematological examination results showed anemia and leukocytosis. The results of the rapid test kit examination showed a positive FPV result. Based on clinical symptoms and the results of investigations, the patient was diagnosed as positive for Feline Panleukopenia Virus. Treatment of FPV is carried out with supportive therapy. Therapy was carried out for 7 days. On the seventh day, based on the results of the hematological examination and the patient's body condition, his condition progressed and he was allowed to continue outpatient therapy.